High school competitive diving injuries: National Athletic Treatment Injury and Outcomes Network (NATION) - Braid, S. M.; Schussler, E. (The Sport Journal, 2020)
Purpose: Elite diving coaches and USA diving officials have become increasingly concerned about injury prevention among adolescent divers. However, little is known about such injuries. The purpose of this study was to describe the injuries among high school students who participated on high school diving teams.